Two-step purification of elastin-like polypeptide-fusion superoxide dismutase via hydrophobicity and thermoresponsiveness - Wang, Weiwei; Chen, Jinping; Zhu, Hao; Huang, Aixia; Zhou, Dongren; Wang, Yuchen; Zhou, Yang; Lin, Feng; Dong, Xiangai; Wu, Yu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSuperoxide dismutase (SOD) catalyzes the dismutation of superoxide radicals to oxygen and hydrogen peroxide, serving as a key antioxidant enzyme with important therapeutic and industrial applications. However, the purification of recombinant SOD remains challenging due to low expression levels and the complexity of traditional purification methods, which involve time-consuming and multi-step chromatography. Elastin-like polypeptides (ELPs) offer a promising alternative due to their hydrophobic and thermoresponsive properties, which can be leveraged for non-chromatographic purification.MethodsA fusion protein of human SOD and an ELP tag (hSOD-ELP) was produced. The purification strategy consisted of two sequential steps. First, foam separation was employed, exploiting the hydrophobicity of the ELP to selectively adsorb hSOD-ELP at the gas-liquid interface. Second, inverse transition cycling (ITC) was used to further purify hSOD-ELP by exploiting ELP’s thermoresponsiveness.ResultsUnder optimized conditions (0.4 mg/mL protein, 30 °C), the initial foam separation step achieved an enrichment ratio of 1.93, a protein recovery of 85.67%, an enzyme activity enrichment of 2.15, and an activity recovery of 93.32%. The subsequent ITC step yielded a recovery rate of 91.98% and a purification fold of 17.45. The cumulative two-step process resulted in a total yield of 85.84% and overall purification fold of 37.52, yielding the purified hSOD-ELP with a final purity of approximately 85%.DiscussionThese results demonstrate that ELP-mediated purification offers a scalable and economical alternative to conventional methods. The combination of foam separation and thermal precipitation minimizes the need for expensive chromatography, making this strategy particularly promising for industrial-scale biotechnological applications.